2012
DOI: 10.1100/2012/342468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aflatoxin on Some Haematological Parameters and Protective Effectiveness of Esterified Glucomannan in Merino Rams

Abstract: The objective of the present study was to evaluate the toxic effects of aflatoxin on some hematological parameters and to determine the preventive effectiveness of added glucomannan. In the study, 32 Merino rams were used, and the rams were separated equally to four groups as control (C), glucomannan (G), glucomannan + aflatoxin (AG), and aflatoxin (A). Erythrocyte, leukocyte count, hemoglobin, and hematocrit levels were decreased in A group compared with the other groups, and there was a reduction in similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
5
24
1
Order By: Relevance
“…This decrease in haematological factors may be due to many causes such as decrease in iron binding capacity (Abdel-Wahhab et al 2002) and hematopoietic defects in blood cells induced by aflatoxins. The haematological results of the present study are in agreement with the studies of Donmez et al (2012) who reported decreased levels of TEC, TLC, HCT and HGB in rams fed on as AFB 1 (250 μg) con-taminated diet. Of the two liver tonics, Silymarin worked more efficiently than choline chloride in treating the effects induced by AFB 1 .…”
Section: Discussionsupporting
confidence: 83%
“…This decrease in haematological factors may be due to many causes such as decrease in iron binding capacity (Abdel-Wahhab et al 2002) and hematopoietic defects in blood cells induced by aflatoxins. The haematological results of the present study are in agreement with the studies of Donmez et al (2012) who reported decreased levels of TEC, TLC, HCT and HGB in rams fed on as AFB 1 (250 μg) con-taminated diet. Of the two liver tonics, Silymarin worked more efficiently than choline chloride in treating the effects induced by AFB 1 .…”
Section: Discussionsupporting
confidence: 83%
“…This decrease in haematological parameters may have many causes, such as a decrease in iron binding capacity (Abdel-Wahhab et al, 2002) and aflatoxin-induced haematopoietic defects in blood cells. The haematological findings of the present study are in agreement with the studies of Donmez et al (2012), who reported decreased levels of TEC, TLC, HGB, and HCT in rams fed a 250 µg AFB1-contaminated diet.…”
Section: Discussionsupporting
confidence: 83%
“…Our studies also correlate with Donmez et al (2012), who found that supplementation of glucomannan at an inclusion level of 1 g per day to an aflatoxin-contaminated diet significantly offset the decrease in haematological parameters, but could not bring them to normal levels.…”
Section: Discussionsupporting
confidence: 74%
“…Poultry have got the ability to synthesize and to modify Vitamin C which mainly caused by the environmental and pathological stressors (McDowell, 2000). Zinc is a cofactor of SOD and at its low concentration can considerably affecting the immune system both in human and animals (Dönmez et al, 2012). Selenium is an essential trace mineral in immune system and is also a cofactor of GPX.…”
Section: Research Articlementioning
confidence: 99%